2021
DOI: 10.1073/pnas.2025320118
|View full text |Cite
|
Sign up to set email alerts
|

Functional cross-talk between phosphorylation and disease-causing mutations in the cardiac sodium channel Na v 1.5

Abstract: The voltage-gated sodium channel Nav1.5 initiates the cardiac action potential. Alterations of its activation and inactivation properties due to mutations can cause severe, life-threatening arrhythmias. Yet despite intensive research efforts, many functional aspects of this cardiac channel remain poorly understood. For instance, Nav1.5 undergoes extensive posttranslational modification in vivo, but the functional significance of these modifications is largely unexplored, especially under pathological condition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…Another limitation of heterologously expressed proteins is the difficulty in controlling post-translational modifications, such as phosphorylation, that impact Na v 1.5 function and 14-3-3 signaling. A recent study reported a successful semisynthetic approach to stabilize Na v 1.5 phosphorylation in vitro 29 . Thus, it would be interesting to test difopein-mediated regulation under stably phosphorylated Na v 1.5.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of heterologously expressed proteins is the difficulty in controlling post-translational modifications, such as phosphorylation, that impact Na v 1.5 function and 14-3-3 signaling. A recent study reported a successful semisynthetic approach to stabilize Na v 1.5 phosphorylation in vitro 29 . Thus, it would be interesting to test difopein-mediated regulation under stably phosphorylated Na v 1.5.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the clear association between heart failure and arrhythmias, widely applicable treatments to simultaneously treat both diseases have been difficult to develop. Rather than targeting and modulating the ion channels themselves, targeting the posttranslational modifications of ion channels, which have more subtle effects on excitability, might prove to be an interesting alternative to treat arrhythmias (Galleano et al, 2021). Therefore, the benefits of PRMT1 on CaMKII and I Ks in cardiomyocytes open the possibility of using the PRMT1 signaling pathway as a novel therapeutic target for treating both heart failure and arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both structural models and native structures represent only snapshots of the full spectrum of protein dynamics. Using static ion channel structures as inputs for molecular dynamics simulations can provide a broader perspective of the dynamics underlying the ion channel gating and modulation (Flood et al, 2019; Galleano et al, 2021; Nguyen et al, 2019; Rovšnik et al, 2021; Suma et al, 2020). Finally, structure-guided computational protein design has achieved significant milestones in recent years (Anishchenko et al, 2021; Cao et al, 2020, 2022; Sahtoe et al, 2022; Silva et al, 2019), and these approaches can be applied to engineer ion channels (Xu et al, 2020; Yang et al, 2016) or design novel ion channel modulators (Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%